HUBUNGAN PENGETAHUAN PREMENSTRUAL SYNDROME DENGAN TINGKAT KECEMASAN PADA REMAJA PUTRI DI SD NEGERI KAUMAN DAN SD NEGERI PUNGKURAN PLERET BANTUL YOGYAKARTA - Endar Timiyatun; I Made Moh. Yanuar Saifudin; Ibna Dzakia Rahmayanti; Eka Oktavianto (Universitas Kusuma Husada Surakarta, 2021)
Anxiety is a nonspecific symptom that is often found and often is a normal emotion. Teenagers who experience puberty will be more depressed, worried, anxious, angry, and crying just because of very little incitement. The aim of this studi was to determine the relationship of knowledge of premenstrual syndrome (PMS) with anxiety levels in adolescent girls. This study used quantitative research methods, the number of samples as many as 30 people who have experienced menstruation and who have experienced premenstrual syndrome total sampling technique. Testing data uses kendall’s know. This study was conducted in Kauman State Elementary School and Pungkuran Pleret State Elementary School in Yogyakarta totaling 30 respondents, the majority of them were 12 years old with 15 respondents (50.0%) and had never received information, as many as 16 respondents (53.3%), and the majority less knowledgeable respondents as many as 15 respondents (53.3%), and experienced severe anxiety as many as 12 respondents (40.0%). Respondents who experienced less knowledge and experienced severe anxiety were 12 respondents (75%). From the result of Kendall's analysis test, it is found that the value of p = 0,000 with a correlation value of 0.800 which means that Ha is accepted and H0 is rejected. There is a relationship between premenstrual syndrome (PMS) knowledge and anxiety levels in adolescent girls.